Divergent preferences and legislative speeches on Brexit. Issue 2 (2nd April 2020) - Umit, Resul; Auel, Katrin
ABSTRACT: How do legislators deal with having preferences that go against those of the principals that they represent in parliament? This article analyzes the debate in the aftermath of the Brexit referendum in the House of Commons to explore the relationship between divergent preferences and legislative speeches. It finds that legislators who defy the will of their country or constituency are rather communicative, and their speeches reveal higher levels of negativity. In contrast, those defying their party refrain from speaking in parliament, but if they speak, they use a significantly less negative language. These findings suggest that legislators behave strategically in deciding whether and how to justify their positions publicly when in conflict with their various principals.